Error Bounds In Approximating Time-Delay Systems - Al-Amer, Samir (2020)
In this paper, bounds on approximating time-delay systems are proposed. Bounds on the infinity norm of the weighted error are obtained when the approximating function is a general rational function, all-pass function, Pade' and Laguerre approximations. An example is presented in illustration.